Composition useful as a temporary fixative
Patent Information
- Application Number
- CN202280048633.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-09
- Filing Date
- 2022-03-03
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-03-03
Smart Images

Figure BDA0004655314350000101
Abstract
Description
[0001] This invention relates to a composition that can be used as a temporary fixative in the field of electronics.
[0002] Patent documents such as EP 3 276 652 A2, WO 2017 / 060140 A2, and WO 2019 / 170213 A1 disclose compositions that can be used as temporary fixatives (pre-fixatives) in the electronics field. These compositions can be used to temporarily fix (pre-fix) a structure consisting of one or more electronic components and one or more solder preforms or sinter preforms that is not yet firmly connected. The temporarily fixed structure can then be firmly connected by a corresponding heat treatment or temperature treatment, i.e., by welding or by sintering. For example, the temporary fixative can be used to temporarily fix a solder preform to be converted into a solder deposit onto an electronic component, or to temporarily fix a sinter preform onto an electronic component, or to temporarily fix a solder preform or sinter preform between electronic components. However, the temporary fixative can also be used, for example, to temporarily fix one electronic component onto the solder deposit of another electronic component equipped with a solder deposit. The temporarily fixed structure is typically heat-treated or temperature-treated in a furnace. In the case of a structure that includes a temporarily fixed sintered preform, the furnace may be, for example, a pressure sintering furnace; in the case of a structure that includes a temporarily fixed solder preform or solder deposit, the furnace may be, for example, a reflow furnace.
[0003] Finally, temporary fixatives can also be used, for example, to provide temporary fixatives to solder deposits on the outward-facing free contact surfaces of electronic components.
[0004] The concept of a "firmly connected structure" is used here. This refers to a structure that is firmly connected mechanically. A firmly connected metal structure is, of course, also conductive. In other words, the contact surfaces of a firmly connected structure are not only firmly connected mechanically, but also electrically connected.
[0005] As used herein, the concept of "solder preform" refers to solder metal in the form of a shaped part, such as solder foil, solder strip, solder sheet, or solder pillar. The solder preform has discontinuous contact surfaces, such as contact surfaces located on opposite sides of the solder preform. The thickness of the solder preform can, for example, range from 10 μm to 750 μm.
[0006] The solder or solder metal is, for example, tin or a tin-rich alloy. Examples of tin-rich alloys are those with a tin content ranging from 90% to 99.5% by weight. Examples of alloy metals are copper, silver, indium, germanium, nickel, lead, bismuth, and antimony. The alloy may be lead-containing or lead-free. Lead-free alloys may be selected, for example, from the group consisting of SnAg, SnBi, SnSb, SnAgCu, SnCu, SnSb, InSnCd, InBiSn, InSn, BiSnAg, or SnAgCuBiSbNi. Lead-containing alloys may be selected, for example, from the group including SnPb and SnPbAg. The melting temperature of the solder may be, for example, in the range of 150°C to 500°C, particularly 170°C to 350°C.
[0007] The concept of "sintered preform" as used herein refers to sintered materials that are not fully sintered, such as sintered metal foil, but specifically to sintering paste that has been dried and is either unsintered or only pre-sintered. The sintering material or sintering paste can be a metallic sintering material or a metallic sintering paste. The metal in a metallic sintering material or metallic sintering paste can be, in particular, copper or silver. In the case of metallic sintering paste, copper or silver is typically in granular form.
[0008] The concept of "solder deposit" as used herein refers to solder that is firmly bonded to the contact surfaces of an electronic component, used for a firm connection to this other electronic component via the contact surfaces of another electronic component. Solder deposits on electronic components are typically manufactured by melting solder, such as applied solder paste or placed solder preforms or solder metals included above, applied to the contact surfaces of the electronic component, followed by cooling as the solder metal solidifies. The solidified solder metal bonded to the contact surfaces of the electronic component is called a solder deposit. Solder deposits bonded to the contact surfaces of electronic components have outward-facing free contact surfaces, thus serving as soldering material for establishing soldered connections with other electronic components. For this purpose, the solder deposit can be melted into molten solder in a furnace such as a reflow oven, and after leaving the furnace, cooling, and solidifying, the desired firm interconnection of the electronic components is formed.
[0009] As used herein, the concept of "electronic component" refers to substrates and active or passive electronic devices commonly used in electronic devices, which are preferably not further disassembled. Electronic components have contact surfaces, particularly metallic contact surfaces.
[0010] Examples of substrates include IMS substrates (insulated metal-substrate), AMB substrates (active metal brazed-substrate), DCB substrates (direct copper-bonded-substrate), ceramic substrates, PCBs (printed circuit boards), and lead frames.
[0011] Examples of active electronic devices include diodes, LEDs (light emitting diodes), dies (semiconductor chips), IGBTs (insulated-gate bipolar transistors), ICs (integrated circuits), and MOSFETs (metal-oxide-semiconductor field-effect transistors).
[0012] Examples of passive electronic devices include sensors, base plates, heat sinks, connecting elements (such as clips), resistors, capacitors, inductors, and antennas.
[0013] The problem is that when moving or transporting any of the embodiments described at the beginning of this document that are not yet securely connected, such as when being fed into a furnace, undesirable positional changes may occur between the preform and the electronic components; the same situation exists when moving or transporting a structure consisting of electronic components equipped with solder deposits and other electronic components to be connected thereto. In the most unfavorable case, the electronic components may not only move or deflect relative to the preform or the electronic components to be connected, or relative to the solder deposit, but may even separate and detach. Causes may include, for example, vibration during transport or acceleration or braking operations. In this case, a remedy may be temporary fixation using a temporary fixative, as described at the beginning of this document.
[0014] The object of this invention is to provide a temporary fixative applicable in the electronics field as described above, which has advantageous viscosity characteristics and exhibits the lowest possible tendency to run after application. The desired temporary fixative should possess a high flow limit to ensure application in a positionally and shape-stable manner. The viscosity characteristics of the desired temporary fixative are particularly important if applied using methods that induce shear stress, such as dispensing or spraying. The temporary fixative should maintain shape and position stability as much as possible after application and contribute to the process reliability of pre-fixation processes implemented industrially using this temporary fixative. Furthermore, the desired temporary fixative should cause minimal wear on the application tools, which also contributes to process reliability or process stability. Moreover, especially outside of the application process, the desired temporary fixative should not cause damage to the surfaces it contacts.
[0015] The solution of the present invention to achieve the above-mentioned objective is to provide a composition as described below. Therefore, the present invention relates to a composition that can be used as a temporary fixative, particularly as a temporary fixative in the electronics field. It should be noted that the concept of "composition of the present invention" used herein refers to a temporary fixative in its original state, i.e., before application. The concept of "temporary fixative" can be used to refer both to the original composition of the present invention and to materials formed based on the composition during or after application due to the partial or complete loss of volatile substances. The volatile substances mentioned can in particular be the organic solvents originally contained in the original composition of the present invention.
[0016] The composition of the present invention comprises the following:
[0017] (A) 20% to 30% by weight, preferably 22% to 28% by weight, of one or more thermoplastic polymers.
[0018] (B) 45% to 69% by weight, preferably 50% to 65% by weight, of organic solvents.
[0019] (C) 2% to 15% by weight, preferably 5% to 9% by weight, of silica particles.
[0020] (D) 0.5% to 10% by weight, preferably 1% to 4% by weight, of an organic thickener.
[0021] (E) 1% to 10% by weight, preferably 5% to 8% by weight, of particulate inorganic fillers having a Mohs hardness in the range of 1 to 8, and
[0022] (F) 0% to 1% by weight, preferably 0% to 0.5% by weight, of one or more components different from components (A) to (E).
[0023] In a preferred embodiment, the composition of the present invention comprises the following:
[0024] (A) 22% to 28% by weight of one or more thermoplastic polymers,
[0025] (B) 50% to 65% by weight of organic solvents,
[0026] (C) 5% to 9% by weight of silica particles,
[0027] (D) 1% to 4% by weight of organic thickener,
[0028] (E) 5% to 8% by weight of particulate inorganic fillers having a Mohs hardness in the range of 1 to 8, and
[0029] (F) 0 to 0.5% by weight, particularly 0.1 to 0.5% by weight, of one or more components different from said components (A) to (E).
[0030] The compositions of the present invention comprise (A) 20 to 30 wt%, preferably 22 to 28 wt%, of one or more thermoplastic polymers. Examples include thermoplastic polyesters, polyurethanes, and (meth)acrylic copolymers, as well as mixtures of these polymer types.
[0031] Preferred thermoplastic polymers are thermoplastic (meth)acrylic copolymers. "(meth)acrylic" means "methacrylic" and / or "acrylic". It is a copolymer of (meth)acrylic compounds, wherein the copolymer may also include non-(meth)acrylic copolymers, such as copolymers of vinyl compounds, whose total weight percentage relative to the whole (meth)acrylic copolymer is <50% by weight. Examples of (meth)acrylic compounds comprising >50% by weight relative to the whole (meth)acrylic copolymer are (meth)acrylic acid, (meth)acrylates, and (meth)acrylamide. Examples of vinyl compounds include compounds such as vinyl esters, vinyl ethers, styrene, and similar compounds.
[0032] Preferably, component (A) of the composition of the present invention is composed of one or more thermoplastic (meth)acrylic copolymers.
[0033] The thermoplastic polymer may have a glass transition temperature, for example, in the range of 40°C to 100°C. The glass transition temperature can be determined by DSC (differential scanning calorimetry) at a heating rate of 10 K / min according to DIN EN ISO 11357-1.
[0034] Unless otherwise stated, all standards cited in this document are the latest versions as of the application date.
[0035] The thermoplastic polymer may have a weight-average molar mass Mw, for example, in the range of 30,000 to 180,000. The weight-average molar mass Mw can be determined according to DIN 55672-1 using GPC (gel permeation chromatography, polystyrene standard, polystyrene gel as stationary phase, tetrahydrofuran as mobile phase).
[0036] The thermoplastic polymer may be without acid groups, or may have acid groups corresponding to an acid value of, for example, <50 mg KOH / g, preferably <25 mg KOH / g, and particularly <10 mg KOH / g; particularly preferably, the thermoplastic polymer is without acid groups and has no acid value. The term "acid group" as used herein refers to a proton donor that is capable of forming H₃O in water. + Functional groups of ions, such as carboxyl groups, sulfonic acid groups, and the like. The determination of acid value, such as carboxyl value, of organic polymers is known to those skilled in the art, for example, according to DIN EN ISO 2114.
[0037] The thermoplastic polymer is soluble in an organic solvent (B); in other words, in the composition of the present invention, component (A) exists in a form dissolved in component (B).
[0038] The compositions of the present invention comprise (B) 45% to 69% by weight, preferably 50% to 65% by weight, of an organic solvent. The organic solvent (B) is particularly an organic solvent with a boiling point ≤285°C. Examples include aliphatic compounds such as toluene and xylene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; esters such as ethyl acetate, isobutyl acetate, and dimethyl succinate; glycol ethers such as diethylene glycol monobutyl ether; alcohols such as benzyl alcohol; and especially terpineol.
[0039] The compositions of the present invention comprise (C) 2% to 15% by weight, preferably 5% to 9% by weight, silica particles. The silica particles serve as an inorganic thickener. The silica particles may have, for example, a particle size of 50 μm. 2 / g to 500m 2 Specific surface area within the range of / g. Specific surface area (unit: m²) 2 The silica particles (d50) can be determined by BET measurement according to DIN ISO 9277 (according to section 6.3.1, static volumetric measurement method, gas used: nitrogen). The silica particles may have an average particle size (d50) in, for example, the range of 5 to 50 nm.
[0040] The concept of "average particle size" used here refers to the average particle diameter (d50) that can be determined by laser diffraction. Laser diffraction measurements can be performed using appropriate particle size measurement equipment, such as the Malvern Instruments Mastersizer 3000.
[0041] The compositions of the present invention comprise (D) 0.5% to 10% by weight, preferably 1% to 4% by weight, of an organic thickener. The organic thickener may be one or more different organic thickeners in combination, particularly organic thickeners, organic anti-sagging agents, and / or organic thixotropic agents known to those skilled in the art for solvent-based non-aqueous coatings. Examples include hydrogenated castor oil, modified fatty acid derivatives, cellulose derivatives (such as ethyl cellulose), diamides, polyamides, diureas, and polyureas. Preferably, component (D) consists of one or more cellulose derivatives, particularly ethyl cellulose.
[0042] The organic thickener (D) can be completely or colloidally dissolved in the organic solvent (B); in other words, in the composition of the present invention, component (D) can be present in a form that is completely or colloidally dissolved in component (B).
[0043] The compositions of the present invention comprise (E) 1% to 10% by weight, preferably 5% to 8% by weight, of a particulate inorganic filler having a Mohs hardness in the range of 1 to 8. The particulate inorganic filler may be particles of one or more different inorganic fillers having a Mohs hardness in the range of 1 to 8. Preferably, inorganic fillers having a Mohs hardness in the range of 1 to 6, particularly 1 to 4, are used. Examples of suitable inorganic fillers include zirconium silicate, quartz, titanium dioxide, mica, calcium silicate, kaolin, and α-boron nitride. α-boron nitride is a particularly preferred example and may also be the sole (E) type inorganic filler contained in the compositions of the present invention. The inorganic filler is present in particulate form, with an average particle size (d50) in the range of, for example, 5 μm to 20 μm, preferably 5 μm to 10 μm.
[0044] Component (E) does not include silica particles.
[0045] The compositions of the present invention may include (F) 0% to 1% by weight, preferably 0% to 0.5% by weight, one or more components different from components (A) to (E). Examples include dyes and additives, particularly additives known to those skilled in the art for solvent-based non-aqueous coating agents. Additives that affect surface tension, such as wetting additives, are particularly noteworthy here. Preferably, component (F) and the compositions of the present invention do not include alumina particles.
[0046] The compositions of the present invention can be prepared by mixing components (A) to (E) or (A) to (F).
[0047] The viscosity properties of the compositions of the present invention can, of course, be affected by all of their components. However, it is important to note that the compositions of the present invention comprise both components (C) and (D).
[0048] The compositions of the present invention are characterized by a high flow limit τ0 within a relative temperature range, for example, from 20°C to 80°C. Accordingly, the flow limit τ0 of the compositions of the present invention is, for example, in the range of 200 Pa to 300 Pa at 23°C, in the range of 90 Pa to 200 Pa at 50°C, and in the range of 40 Pa to 100 Pa at 75°C. The flow limit τ0 at the corresponding temperatures can be determined, for example, by rotational viscosity measurement, using, for example, the cone-plate measurement principle, wherein the cone diameter is 25 mm, the cone angle is 2°, the measuring gap is 104 μm, and, for example, within 0.05 s in 15 minutes. -1 up to 50s -1 The shear rate that increases uniformly within a certain range.
[0049] The composition or temporary fixative of the present invention is viscous, meaning it remains viscous even when used as a temporary fixative, i.e., during application and when creating a temporarily fixed structure, and even within a temperature range of, for example, 60°C to 130°C. In this stage, the glass transition temperature of the thermoplastic polymer (A) and the proportion of the organic solvent (B) have a significant impact on the adhesive effect.
[0050] The compositions of the present invention are suitable, particularly in the field of electronics, for use as temporary fixatives.
[0051] The compositions of the present invention can be used to temporarily fix a structure, which is not yet securely connected and consists of one or more electronic components and one or more solder preforms or sintered preforms. For example, the compositions of the present invention can be used to temporarily fix a solder preform or sintered preform to be converted into a solder deposit onto an electronic component; in this case, the temporarily fixed structure comprises or is constituted by: an electronic component and a solder preform to be converted into a solder deposit, or an electronic component and a sintered preform, with a temporary fixing agent provided between the electronic component and the corresponding preform. The compositions of the present invention can also be used to fix solder preforms or sintered preforms between electronic components; in this case, the temporarily fixed structure may include or be constituted by an electronic component with a solder preform or sintered preform in the middle, and with a temporary fixing agent provided between at least one of the preform and the electronic component.
[0052] However, the composition of the present invention can also be used to temporarily fix an electronic component to another electronic component equipped with solder deposits; in this case, the temporarily fixed structure includes or is constituted by the following: a first electronic component located on the solder deposit of another electronic component equipped with solder deposits, wherein a temporary fixing agent is provided between the first electronic component and the solder deposit, or more precisely, between the originally outward-facing free contact surfaces of the solder deposits of the first electronic component and the other electronic component.
[0053] The compositions of the present invention can also be used to: provide a temporary fixative for solder deposits on the outward-facing free contact surfaces of electronic components.
[0054] In all the foregoing uses, the composition or temporary fixative of the present invention is applied to at least one contact surface. The contact surface includes the contact surface of electronic components, but also includes the contact surface of the aforementioned solder preform or sintered preform, or the outward-facing free contact surface of solder deposits.
[0055] In all the foregoing uses, the compositions of the present invention can be applied using various application processes, such as dipping, dispensing, or spraying, particularly dispensing or spraying. As mentioned above, the application location is the contact surface.
[0056] Preferably, the composition of the invention is applied under heating conditions, for example at a temperature in the range of 45°C to 75°C, that is, the composition of the invention is removed from the application tool in a manner that is heated to the corresponding temperature. As described at the beginning of this document, the composition of the invention is also sheared during the application process by means of preferred dispensing or spraying.
[0057] The advantageous properties of the compositions of the present invention are particularly evident during application using preferred dispensing or spraying methods; the compositions of the present invention result in only minor wear on the corresponding application tools. For example, worn parts, such as nozzles, push rods, or screw-type metering valves, only need to be replaced after a relatively long period of use.
[0058] The compositions of the present invention can be applied, for example, in strip form to the side of the preform, but particularly in the form of dots, for example, in hemispherical or similar dot shapes. Immediately after application, the height of the dots can be, for example, in the range of 50 μm to 80 μm. Immediately after application, the diameter of the dots can be, for example, in the range of 200 μm to 1000 μm.
[0059] During the journey from the application tool to the application site, the composition of the present invention, which serves as a temporary fixative, may lose some of its original organic solvent (B) due to evaporation loss.
[0060] After applying the composition of the present invention, drying may be performed first to partially or completely remove the contained organic solvent (B). Alternatively, after applying the composition of the present invention, a desired temporarily fixed structure may be created according to one of the foregoing embodiments, followed by drying. For example, drying may be performed at an object temperature of 90°C to 150°C for 2 to 30 minutes. Drying may also be omitted, i.e., passive drying may be allowed without active drying measures.
[0061] As mentioned earlier in the description of the bonding effect, the proportion of the organic solvent (B) is a crucial factor affecting the bonding effect. Those skilled in the art can influence the bonding effect by selecting drying parameters. The temperature conditions under which the temporarily fixed structure is transported and / or stored are also considered. This is generally done within a temperature range of, for example, 18 to 28°C. Those skilled in the art consider the same issue with electronic components equipped with solder deposits, where a temporary fixative is applied to the outward-facing free contact surfaces of the solder deposits.
[0062] As a result of using the compositions of the present invention as temporary fixatives in the electronics field, the present invention also relates to an electronic component equipped with solder deposits, wherein a temporary fixative applied with the compositions of the present invention is provided on the outward-facing free contact surfaces of the solder deposits. In this embodiment, the organic solvent (B) originally contained in the compositions of the present invention is either entirely present in the temporary fixative or is typically partially or completely removed.
[0063] As a further consequence of using the compositions of the present invention as temporary fixatives in the field of electronics, the present invention also relates to temporarily fixed structures according to all the foregoing embodiments. In particular, examples (1) to (5) are included:
[0064] (1) A temporarily fixed structure consisting of an electronic component and a solder preform, wherein a temporary fixing agent applied with the composition of the present invention is provided between the electronic component and the solder preform.
[0065] (2) A temporarily fixed structure consisting of an electronic component and a sintered preform, wherein a temporary fixing agent applied with the composition of the present invention is provided between the electronic component and the sintered preform.
[0066] (3) A temporarily fixed structure comprising electronic components including one or more sintered preforms disposed in the middle, wherein a temporary fixing agent applied with the composition of the present invention is provided between at least one of the electronic components and the sintered preform or at least one of the sintered preforms.
[0067] (4) A temporarily fixed structure consisting of electronic components comprising one or more solder preforms disposed in the middle, wherein a temporary fixing agent applied with the composition of the present invention is provided between at least one of the electronic components and the solder preform or at least one of the solder preforms.
[0068] (5) A temporarily fixed structure consisting of a first electronic component, the first electronic component being located on the solder deposit of another electronic component equipped with solder deposit, wherein a temporary fixing agent applied with the composition of the present invention is provided between the first electronic component and the solder deposit.
[0069] In all the temporarily fixed configurations in Examples (1) to (5), the organic solvent (B) originally contained in the composition of the present invention may be present in the temporary fixative intact, or may be partially or completely removed.
[0070] Finally, in order to transition from a temporarily fixed state to a firmly connected state through welding or sintering, the temporarily fixed structure, such as the structures according to the aforementioned examples (1) to (5), may be subjected to corresponding heat treatment or temperature treatment. During the heat treatment or temperature treatment, the temporary fixative may be removed, leaving only non-disturbing inorganic residues in the form of silica particles and inorganic filler particles. Example:
[0071] To prepare an exemplary temporary fixative, a thermoplastic (meth)acrylic copolymer, α-terpineol, and ethyl cellulose were mixed at 70°C to 80°C in the proportions given in Table 1 until all components were dissolved. Inorganic filler particles and silica particles were then added while stirring, and the mixture was expanded at 70°C to 80°C for 10 minutes. The temporary fixative exhibited Carson flow characteristics.
[0072] At three different temperatures (23℃, 50℃, and 75℃), using a Physika / MCR 301 rheometer (cone-plate measurement principle, cone diameter 25mm, cone angle 2°, measurement gap 104μm), a result was obtained within 0.05s over 15 minutes. -1 up to 50s -1 (Viscosity is measured by uniformly increasing shear rate within a certain range) to determine the flow limit τ0.
[0073] Table 1: Composition of the temporary fixatives (E1 and E2) of the present invention and three comparative examples (V1, V2 and V3)
[0074]
[0075] Compared to comparative compositions V1-V3, a greater number of dispensing operations can be achieved using the temporary fixatives E1 and E2 of the present invention until the screw metering valve in the dispensing machine wears out.
Claims
1. A composition comprising: (A) 20% to 30% by weight of one or more thermoplastic polymers, (B) 45% to 69% by weight of organic solvents. (C) 2% to 15% by weight of silica particles, (D) 0.5% to 10% by weight of organic thickener, (E) 1% to 10% by weight of particulate inorganic fillers having a Mohs hardness in the range of 1 to 8, and (F) 0% to 1% by weight of one or more components different from components (A) to (E).
2. The composition according to claim 1, wherein the composition comprises: (A) 22% to 28% by weight of one or more thermoplastic polymers, (B) 50% to 65% by weight of organic solvents. (C) 5% to 9% by weight of silica particles, (D) 1% to 4% by weight of organic thickener. (E) 5% to 8% by weight of particulate inorganic fillers having a Mohs hardness in the range of 1 to 8, and (F) 0% to 0.5% by weight of one or more components different from components (A) to (E).
3. The composition according to claim 1 or 2, wherein, The thermoplastic polymer is selected from the group consisting of thermoplastic polyesters, thermoplastic polyurethanes, thermoplastic (meth)acrylic copolymers, and thermoplastic mixtures of these polymer types.
4. The composition according to claim 1 or 2, wherein, The particulate inorganic filler of component (E) is selected from the group consisting of zirconium silicate, quartz, titanium dioxide, mica, calcium silicate, kaolin and α-boron nitride.
5. The composition according to claim 4, wherein, Component (E) is α-boron nitride.
6. Use of a composition according to any one of the preceding claims as a temporary fixative in the field of electronics.
7. The use according to claim 6, for temporarily fixing a structure which is not yet securely connected to one or more electronic components and one or more solder preforms or sinter preforms, or for temporarily fixing an electronic component to another electronic component equipped with solder deposits.
8. Use of the composition according to any one of claims 1 to 5 for providing a temporary fixative on the outward-facing free contact surface of solder deposits on electronic components.
9. The use according to any one of claims 6 to 8, wherein, The composition is applied by dipping, dispensing, or spraying.
10. The use according to claim 9, wherein, The composition is applied at a temperature in the range of 45 to 75°C.
11. A structure that is not yet firmly connected, consisting of one or more electronic components and one or more solder preforms or sinter preforms, which can be obtained as a result of the use according to claim 7, or an electronic component that can be temporarily fixed to another electronic component equipped with solder deposits.
12. An electronic component equipped with a solder deposit, which can be obtained as a result of the use according to claim 8, wherein the temporary fixative is provided on the outward-facing free contact surface of the solder deposit.
Citation Information
Patent Citations
Method for producing a substrate arrangement with a glue prefixing means, corresponding substrate arrangement, method for connecting an electronic component with a substrate arrangement using a glue prefixing means formed on the electronic component and / or the substrate arrangement and an electronic component bonded with a substrate arrangement
EP3276652A2
Method for producing a substrate arrangement, substrate arrangement, and method for connecting a substrate arrangement to an electronic component
WO2017060140A2
Method for producing a sandwich arrangement
WO2019170213A1
Substrate structure, manufacturing method thereof, electronic component and a method for bonding electronic component with a substrate structure
CN106057690A